Sly fox and little red hen - Giles, Jenny; Lowe, Isabel (South Melbourne : Nelson School, 1998)
Light-hearted stories and fables about talking animals are a very old European tradition. This simple retelling omits the hen's amazing skill with a needle and thread, but retains the original humour of the tale. Set in Britain in the 19th century.
K
540
K
Keywords: Animals; Farm animals; Chicken; Fox